Thyroid disorders and breast cancer risk in Asian population: a nationwide population-based case–control study in Taiwan. Issue 3 (30th March 2018) - Weng, Chien-Hsiang; Chen, Yi-Huei; Lin, Ching-Heng; Luo, Xun; Lin, Tseng-Hsi
Abstract : Objective: To evaluate whether hyperthyroidism or hypothyroidism increases the risk of subsequent breast cancer in an Asian population. Design: Nationwide population-based case–control study. Setting: All healthcare facilities in Taiwan. Participants: A total of 103 466 women (mean age 53.3 years) were enrolled. Methods: 51 733 adult women with newly diagnosed primary breast cancer without a previous cancer history between 2006 and 2011 were identified and included in our study. 51 733 women with no cancer diagnosis prior to the index date were age matched as controls. Diagnosis of hyperthyroidism or hypothyroidism prior to the diagnosis of breast cancer or the same index date was identified, age, histories of thyroid disease treatment, oestrogen use and radioactive iodine treatment were adjusted. Main outcome measures: To identify risk differences in developing breast cancer among patients with a medical history of hyperthyroidism or hypothyroidism. Results: There was a significantly increased risk of breast cancer in women with hyperthyroidism under the age of 55 years (age <45: OR 1.16, P=0.049; age 45–55: OR 1.15, P=0.019). Patients with hypothyroidism also showed an increased risk of breast cancer (OR 1.19, P=0.029) without statistical significance after stratification by age group (age <45, 45–55, >55 years). Treatment for thyroid disorders did not alter the association in subgroup analyses (P=0.857; 0.262, respectively). Conclusions: Asian women under 55 years of age with history of hyperthyroidism have a significantly increased risk of breast cancer regardless of treatment. Women with history of hypothyroidism may also have an increased risk.